A scoping review of the prevalence of antimicrobial-resistant pathogens and signatures in ready-to-eat street foods in Africa: implications for public health - Onohuean, Hope; Olot, Haron; Onohuean, Fanny Eseohe; Bukke, Sarad Pawar Naik; Akinsuyi, Oluwamayowa S.; Kade, Ayomikun (Frontiers in Microbiology, 2025)
Background and objectiveDespite its critical role in individual and societal health, food hygiene remains underexplored. Antibiotic-resistant pathogenic bacteria in ready-to-eat (RTE) food threaten public health. This scoping review collected data on the epidemiological prevalence of RTE food-contaminated pathogens resistant to antimicrobial drugs and resistance genes in Africa.MethodUsing electronic databases, such as PubMed, Scopus, and Web of Science (WoS), handpicked from references, pre-reviewed published articles were retrieved and analyzed according to the PRISMA-ScR guidelines.ResultsThe findings indicate 40 previewed published articles qualified for meta-synthesis in the scoping review with a population/case ratio of 11,653/5,338 (45.80%). The most frequently reported RTE foods were meat or beef/beef-soup, chicken or poultry products, salads, vegetable salads, and sandwiches, which harboured pathogens such as E. coli, Salmonella, and Staphylococcus. Antibiotic susceptibility tests revealed the use of 48 antibiotics to manage infections, following CLSI (Clinical and Laboratory Standards Institute) protocols. Moreover, 10 authors reported 54 resistance genes associated with pathogenic resistant bacteria. In addition, only 15 studies received funding or financial support.ConclusionThese findings from several researchers indicate that RTE street foods in African and resource-limited nations harbour enteric pathogens and are a significant concern to the public health system and reservoir of the spread of antibiotic resistance. This underscores the necessity of implementing effective control strategies to address challenges and limit the spread of resistant bacteria in RTE foods. The antimicrobial resistance surveillance system in the region is a significant concern. Notably, Africa needs to strengthen the national and international regulatory bodies and a health surveillance system on antimicrobial resistance, particularly among developing nations.